Pamięć zbiorowa i polityka pamięci. Prasa polska i niemiecka wobec czterdziestej rocznicy wizyty kanclerza Willy'ego Brandta w Warszawie = Collective memory and the policy of memory the Polish and German press against the 40th anniversary of the visit of chancellor Willy Brandt to Warsaw - Kasztelan, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this article is the analysis of the contents of the Polish and German work in the 40th anniversary of the gesture of the chancellor Willy Brandt in front of the Monument of the Getto Heroes. The published texts were studied in terms of formulating collective memory and perceiving the act of kneeling of the chancellor as the "place of memory". The attention has been concentrated on the fact that periodicals in accordance with the represented orientation, ideological line, fokus on other aspects of the event which took place 40 years ago.
Keywords: stosunki polsko-niemieckie; prasa niemiecka; prasa polska